Part tree, part canoe : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Te Ao, Shannon (Massey University, 2015)
Using Australian artist and writer Ross Gibson's 'wayfinder' as a point of departure this essay discusses a range of recent moving image and performance works by Shannon Te Ao. 𝘍𝘰𝘭𝘭𝘰𝘸 𝘵𝘩𝘦 𝘱𝘢𝘳𝘵𝘺 𝘰𝘧 𝘵𝘩𝘦 𝘸𝘩𝘢𝘭𝘦 (2013), 𝘵𝘸𝘰 𝘴𝘩𝘰𝘰𝘵𝘴 𝘵𝘩𝘢𝘵 𝘴𝘵𝘳𝘦𝘵𝘤𝘩 𝘧𝘢𝘳 𝘰𝘶𝘵 (2014), and 𝘜𝘯𝘵𝘪𝘵𝘭𝘦𝘥 (𝘦𝘱𝘪𝘭𝘰𝘨𝘶𝘦), (2015) are among the works discussed in relation to Maori spatial and temporal conceptions such as 𝘛𝘦 𝘒𝘰𝘳𝘦 and whakapapa. These frameworks, alongside content referencing Maori lyrical traditions are implicated within a discussion exploring various aspects of the local, social and cultural significance of poetic forms found in waiata and whakatauki. Metaphor and ambiguity - as they are enacted in live performance, and lyrical modes - are identified as tools to promote a poetic sensibility.
Keywords: Gibson, Ross; Te Ao, Shannon; Criticism and interpretation; Oceania in art